6.0 V High‐Voltage and Concentrated Electrolyte toward High Energy Density K‐Based Dual‐Graphite Battery. Issue 41 (22nd September 2020) - Li, Xiang; Ou, Xuewu; Tang, Yongbing
Abstract: K‐based dual‐carbon batteries (K‐DCBs) integrate the advantages, including high‐voltage, low‐cost, and environmentally friendliness of dual‐ion batteries (DIBs), and large abundance of K, thus attracting much attention in large‐scale energy storage application. However, most currently used electrolytes based on KPF6 and carbonate solvents commonly suffer from poor oxidation potential (<4.4 V vs Li/Li + ) and low electrolyte concentration (<1 m), which limit the cycling stability and energy density of K‐DCBs. Herein, after a matching behavior study of various electrolyte solvents with potassium salts, a concentrated electrolyte is developed by successfully dissolving 5.2 m potassium bis(fluorosulfonyl)imide into tetramethylene sulfone. This high‐concentration electrolyte exhibits advantages: 1) high oxidation potential that enhances intercalation reversibility and capacity of FSI − anions; 2) improved K + storage at graphite anode; 3) dramatically increased energy density of K‐DCB. A proof‐of‐concept K‐ion dual‐graphite battery based on this high‐concentration electrolyte displays a discharge capacity of 83.4 mAh g −1 at 100 mA g −1, and negligible capacity fading after 300 cycles. Furthermore, considering both the electrolyte and electrode materials, energy density of such K‐DCB reaches ≈130 Wh kg −1, the best performance of K‐DCBs among previously reported research. Abstract : A 5.2 m highly concentrated potassium bis(fluorosulfonyl)imide/tetramethylene sulfone electrolyte is developed for K‐based dual‐graphite batteries. Ascribed to the high oxidation potential (≈6.0 V) that allows the intercalation reversibility of FSI − anions at the graphite cathode and improved K + storage at graphite anode, the K‐based dual‐graphite battery displays significantly enhanced capacity and energy density based on this concentrated electrolyte.